Basic soil mechanics - Whitlow, R. (Harlow, Essex, England : Longman Scientific & Technical ; New York : Wiley, 1995)
Basic Soil Mechanics has long been established as the standard work on the subject for degree and diploma students of civil engineering and building. The third edition has been fully revised and updated to provide students not only with the basic principles but also with an awareness of state-of-the-art developments in the field.
Basic Soil Mechanics is an essential text for BTEC HNC/D and undergraduate degree courses in civil engineering. It will also be a valuable resource for practising engineers engaged in the design and construction of soil-related structures and systems.
The approach to stress/strain behaviour has been reconsidered in the light of modern educational methods and the chapter on earth pressure has been revised to take account of the long-awaited British Standard BS 8002. The book also gives greater emphasis to design methods and the use of computers.
0
Keywords: MCE; Soil mechanics